THE EFFECTIVENESS OF PROBLEM-BASED AND DISCOVERY LEARNING MODELS ON STUDENTS' MATHEMATICAL CRITICAL THINKING ABILITIES - Nurjaman, Adi; Sari, Indah Puspita; Hidayat, Wahyu (KALAMATIKA Jurnal Pendidikan Matematika, 2025)
Critical thinking skills are essential for addressing 21st-century challenges, which requires a learning model that can optimally engage students' cognitive abilities. This study aims to examine the improvement of students' critical mathematical thinking skills (KBKM) through learning that utilizes the Problem-Based Learning (PBL) and Discovery Learning models, based on the students' skill levels. The method used in this study is a mixed-method approach with a sequential explanatory design. In the quantitative phase, quasi-experimental research was conducted with a one-group pretest-posttest design, ANOVA, and a 3x2 factorial design. In the qualitative phase, an embedded concurrent strategy was applied. The sample consisted of 72 grade VII students from State Junior High Schools in Cimahi City. The results revealed that the criteria had a significant effect on the critical mathematical thinking skills scores. The learning model also had a direct impact on improving these skills. Additionally, the study found that the average score of the high group was higher than that of the medium and low groups. In terms of learning models, Discovery Learning proved to be more effective in the learning process.